2014
DOI: 10.1152/ajpcell.00145.2013
|View full text |Cite
|
Sign up to set email alerts
|

PP1γ functionally augments the alternative splicing of CaMKIIδ through interaction with ASF

Abstract: W. PP1␥ functionally augments the alternative splicing of CaMKII␦ through interaction with ASF. Am J Physiol Cell Physiol 306: C167-C177, 2014. First published November 6, 2013 doi:10.1152/ajpcell.00145.2013.-Protein phosphatase 1 (PP1) and Ca 2ϩ /calmodulin-dependent protein kinase ␦ (CaMKII␦) are upregulated in heart disorders. Alternative splicing factor (ASF), a major splice factor for CaMKII␦ splicing, can be regulated by both protein kinase and phosphatase. Here we determine the role of PP1 isoforms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
5
14
0
Order By: Relevance
“…It could also act on splicing since it can interact with components of the spliceosome machinery, known to crosstalk with nuclear miRNA processing43444546. Binding of proteins such as Tra2β1, SF2A, Srp30c and ASF to PP1 through conserved RNA recognizing domains is essential for correct splice site selection4247, and by extension may also affect miRNA processing. Interestingly, a recent study demonstrated a developmentally timed processing of pri-miR-183/96/182 involved in neuronal organization.…”
Section: Discussionmentioning
confidence: 99%
“…It could also act on splicing since it can interact with components of the spliceosome machinery, known to crosstalk with nuclear miRNA processing43444546. Binding of proteins such as Tra2β1, SF2A, Srp30c and ASF to PP1 through conserved RNA recognizing domains is essential for correct splice site selection4247, and by extension may also affect miRNA processing. Interestingly, a recent study demonstrated a developmentally timed processing of pri-miR-183/96/182 involved in neuronal organization.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiomyocytes subjected to ischemia/reperfusion or H 2 O 2 treatment, CaMKII δ C increased and CaMKII δ B decreased rapidly to a new steady‐state within 8 hours of treatment onset . Indeed, regulation of relative CaMKII δ C / δ B expression ratio is likely regulated by numerous factors within the myocyte, including kinase/phosphatase activity and oxygen/glucose availability . Together these findings have provided support for the notion that intra/extracellular environmental factors regulate both the relative expression and activity of the CaMKII δ C / δ B variants and their net influence on cardiomyocyte responses, thereby determining overall cardiomyocyte vulnerability to CaMKII δ ‐driven functional and structural outcomes (i.e.…”
Section: Camkiiδ Splice Variant Actions – An Evolving Understandingmentioning
confidence: 72%
“…Protein kinase A (PKA)-mediated ASF/SF2 phosphorylation has been correlated with alternative splicing of CaMKIIδ in heart and brain (Gu et al, 2011). Additionally, regulation of ASF/SF2 by Protein phosphatase 1 γ (PP1γ) has been demonstrated to affect CaMKIIδ splicing (Huang et al, 2013). CaMKIIδ A expression is increased in models of isoproterenol-induced cardiac hypertrophy and thus regulation of CaMKIIδ splicing by PKA and PP1γ may be relevant in the context of chronic β-adrenergic stimulation (Li et al, 2011).…”
Section: Expression and Localizationmentioning
confidence: 99%